Nuclear- and radiochemistry. - Rösch, Frank (De Gruyter graduate., 2016)
Nuclear chemistry represents a vital field of basic and applied research. Modern applications cover, for example, fundamental aspects of energetics and high-sensitive, high-selective and non-destructive analytical technologies. Nuclear chemistry and radiopharmaceutical chemistry are increasingly used to bridge pharmaceutical and medical research with state-of-the-art non-invasive molecular diagnosis as well as with patient-individual treatment. While volume I on Introduction to Nuclear Chemistry describes the origin of unstable atoms and their pathways to stabilize, this volume II illustrates the spectrum of modern applications of nuclear and radiochemistry. In various chapters, leading scientists address- the measurement of radiation, - the dosimetric action of radioactive radiation and radiation safety- nuclear dating- elemental analysis by neutron activation, - radiation mass spectroscopy and chemicals speciation, - radiochemical separations, - applications of radiochemistry to life sciences, - the chemistry of radioelements: Tc and At, actinides and the transactinides- fundamentals of modern nuclear energy.